(untitled) (Medico Legal Update, 2020)
Effect of Perceived Stress on Menstruation among Adolescent Girls in a Selected College, Kanchipuram District, Tamil Nadu, India. The objectives were to assess the effect of perceived stress on menstruation among adolescent girls in a selected college, Correlate between perceived stress and blood flow during menstruation among adolescent girls, Associate between perceived stress on menstruation among adolescent girls with their selected demographic variables, Associate between blood flow during menstruation among adolescent girls with their selected demographic variables. The convenient sampling technique was used to select 50 samples. The data were collected by using perceived stress scale and pictorial blood assessment scale. The collected data were tabulated and analyzed. Descriptive and inferential statistics were used. The result showed that 12% of samples having low stress level, 80% of samples having moderate stress level and 8% of samples having severe stress level and 16% of samples had low bleeding, 30% of samples had normal flow and 54% of samples had severe flow. There was moderate positive correlation (r = 0.84) between perceived stress and blood flow among adolescent girls. The demographic variables like menstrual cycle periodicity (X2=1.78) stress level, (X2=3.87) blood flow and duration of menstrual flow (X2=4.32) stress level, (X2=5.93) blood flow had significant association with stress and blood flow during menstruation respectively.